How Does the Fast Track Intervention Prevent Adverse Outcomes in Young Adulthood? - Sorensen, Lucy C. (Child Dev, 2015)
Numerous studies have shown that childhood interventions can foster improved outcomes in adulthood. Less well understood is precisely how – that is, through which developmental pathways – these interventions work. This study assesses mechanisms by which the Fast Track project (n=891), a randomized intervention in the early 1990s for high-risk children in four communities (Durham, NC; Nashville, TN; rural PA; and Seattle, WA), reduced delinquency, arrests, and health and mental health service utilization in adolescence through young adulthood (ages 12–20). A decomposition of treatment effects indicates that about a third of Fast Track’s impact on later crime outcomes can be accounted for by improvements in social and self-regulation skills during childhood (ages 6–11), such as prosocial behavior, emotion regulation and problem solving. These skills proved less valuable for the prevention of mental and physical health problems.